THE EFFECT OF OCCUPATIONAL ENVIRONMENT AND LEADERSHIP BEHAVIOR ON EMPLOYEE MORALE AT MATAHARI DEPARTMENT STORE MEGAMALL MANADO - Nepa, Andre Juan; Tulung, Joy Elly; Arie, Fitty V. (Universitas Sam Ratulangi, 2021)
Employees are producers who play an important role in the company's success. The dedication of employees to the company is very influential. Therefore, companies need to consider factors that affect employees at work. Occupational environment and good leadership behaviors factors can improve employee morale. This study aims to identify whether or not a significant effect of occupational environment and leadership behavior on employee morale at Matahari Department Store Megamall Manado. The researcher conducted this research through quantitative methods. The method of analysis used is the multiple linear regressions. The sample used is 69 employees with saturated sampling techniques. The results showed that occupational environment (X1) partially have a significant effect on employee morale (Y), leadership behavior (X2) partially have a significant effect on employee morale (Y) and occupational environment and leadership behavior simultaneously have a significant effect on employee morale at Matahari Department Store Megamall Manado.Â Keywords: occupational environment, leadership behavior, employee morale